2007
DOI: 10.1089/end.2006.0230
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Designed Amplatz Sheath Decreases Intrapelvic Irrigation Pressure During Mini-Percutaneous Nephrolitholapaxy: An in-Vitro Pressure-Measurement and Microscopic Study

Abstract: Newly designed nephroscope sheaths with an open proximal end, such as the one described here, decrease the intrapelvic pressure compared with a closed outflow system. As a result, strict fluid control during the intervention is not necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 12 publications
0
29
0
3
Order By: Relevance
“…The use in adults has been subsequently described by several groups. 6,10,18 Up to now, MPCNL has not been standardized, leading to the fact that sheath diameters below 20F are defined as miniaturized. In fact, Jackmanand colleagues 17 described a technique using an 11F access tract, while Nagele and coworkers 6,10 use 18F and Lahme and associates 18 use 15F.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use in adults has been subsequently described by several groups. 6,10,18 Up to now, MPCNL has not been standardized, leading to the fact that sheath diameters below 20F are defined as miniaturized. In fact, Jackmanand colleagues 17 described a technique using an 11F access tract, while Nagele and coworkers 6,10 use 18F and Lahme and associates 18 use 15F.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques have been described in detail. 6,9,10 Patients were treated in a tubeless fashion after uncomplicated, stone-free MPCNL, with thrombin-matrix tract closure (Floseal, Baxter, Unterschleißheim, Germany) and antegrade Double-J catheter placement as described previously. 7 After standard PCNL, all patients received 22F nephrostomies.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the outflow speed of the lavage fluid should be closely monitored during the operation because the nephrostomy channel selected in the micro-PCNL was <24 Fr, and the gap between the peel-away sheath and 8/9.8 Fr of the ureteroscope was relatively small. In case of a sluggish outflow of the lavage fluid caused by stone clogging, the ureteroscope should be pulled out to clear the residual stones [19,20]. An operation time of 2 h should be strictly observed because "time is bleeding," that is, longer operation may result in bleeding at a large extent and induce absorption of intraoperative liquid and toxins, thereby causing postoperative complications [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the authors' note, despite the fact that no hemorrhage has occurred in a group of 19 patients, miniaturized instruments were associated with significant operative time increase with larger stone masses [19], due to the fact that utilization of a smaller sheaths are associated with more difficult stone fragment retrieval and need of additional tools such as disposable retrieval baskets [4]. It was not until Nagele et al [3] in 2008 reported on a “Newly Designed Amplatz Sheath” (Karl Storz) with the vacuum cleaner effect, which was nicely depicted in a study by Nicklas et al [4]. The basis of this effect lies in Bernoulli's principle, according to which an increase in the speed of a fluid in the constriction zone occurs simultaneously with a decrease in pressure [20], also known as ‘pseudocavity’ which is being located at the tip of the nephroscope during mini-PCNL able to extract stone fragments through access sheath without any additional stone extracting devices [4].…”
Section: Discussionmentioning
confidence: 99%
“…Hickman peel away introduction set. Further advances led to the development of metallic Amplatz sheath with nephroscope, where one of the prominent advantages was vacuum cleaner effect, consistent with hydrodynamic Bernoulli's principle [3]. According to this principle, during mini-PCNL, the front of a low pressure called ‘pseudocavity’ is produced at the tip of nephroscope, which can extract the stone fragments through an access sheath without any additional grasping devices [4].…”
Section: Introductionmentioning
confidence: 99%